The Socio-Economic Implications of Somali Refugees to the Host community at the Dadaab Refugee Camp in Kenya - Somo, Haithar; Kurgat , Dr. Alice; Kwonyike , Joshua (Advances in Social Sciences Research Journal, 2021)
Across the world, refugee hosting has been associated with costs and benefits to the hosting nations. However, in Kenya, hosting Somali refugees is majorly considered costly rather than beneficial to the nation. The county’s high insecurity is one of the major effects that Somali refugees are associated with. No objective research has indicated the specific benefits of Somali refugees in Kenya. Using mixed research method, this study focused on establishing the costs and benefits of Somali refugees. The findings show that Somali refugees pose positive and negative effects on the Kenyan state. These effects are economic, social, and environmental. The study recommends policy implementation and technological adoption strategies as ways of enhancing Somali refugee contribution to Kenya’s socio-economic development.